Sclareolide as Antifungal Strategy Against Cryptococcus neoformans: Unveiling Its Mechanisms of Action - Arumugam Ganeshkumar; Patricia Michelle Nagai de Lima; Jebiti Haribabu; Bruno Montanari Borges; Nycolas Willian Preite; Flavio Vieira Loures; Arunachalam Arulraj; Juliana Campos Junqueira (Microorganisms)
Cryptococcal infection commonly begins as an opportunistic infection in humans, however, this can escalate to a systemic or life-threatening form in immunocompromised individuals. Here, we aim to identify novel antifungal molecules from plants resources. Sclareolide, a phytochemical classified as a sesquiterpene lactone, was assessed against Cryptococcus neoformans H99. Sclareolide exhibited promising antifungal properties with a minimum inhibitory concentration (MIC) of 16 µg/mL. Additionally, the C. neoformans growth rate was significantly affected by sclareolide treatment in a concentration-dependent manner, as observed through a time killing assay, with a significant reduction at MIC × 8 compared to the control by 48 h. To elucidate the underlying mechanisms of sclareolide antifungal activity, fluorescence-based methods were employed. Propidium iodide (PI) accumulation assay indicated a reduction in C. neoformans membrane integrity, with values as low as 6.62 ± 0.18% after treatment. Moreover, sclareolide at MIC × 4 and MIC × 8 significantly increased the production of reactive oxygen species (ROS) and reduced the mitochondrial membrane potential (MMP), suggesting oxidative stress and mitochondrial dysfunction in C. neoformans. Sclareolide did not induce caspase-dependent apoptosis, suggesting a non-apoptotic mechanism. Further, a checkerboard experiment was performed to assess potential synergistic interaction with Amphotericin B, however, no synergism was observed. Moving on, sclareolide at 128 µg/mL did not exhibit toxicity in Galleria mellonella, further supporting its potential as a safe antifungal agent. These findings suggest that the antifungal activity of sclareolide against C. neoformans is mediated by oxidative stress. Further in vivo and pharmacokinetic studies are recommended to explore the potential of sclareolide as a prototype for the development of novel anti-cryptococcal therapies.